2009
DOI: 10.1002/hed.21096
|View full text |Cite
|
Sign up to set email alerts
|

Cost utility of docetaxel as induction chemotherapy followed by chemoradiation in locally advanced squamous cell carcinoma of the head and neck

Abstract: TPF is cost-effective as induction chemotherapy in locally advanced SCCHN compared with PF. Local treatment patterns may impact findings for other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Most of these studies were deemed inappropriate for the derivation of the current model recurrence health states because the majority either reported only utilities derived from the EORTC QLC-C30 questionnaire (a cancer-specific health-related quality-of-life questionnaire), which cannot be easily converted in to EQ-5D utilities, [78][79][80][81] or did not report health state utilities that could be reliably mapped to the health states used in the current model. 82 One UK study 83 was identified. However, this study calculated EQ-5D utilities from a sample of 50 oncology nurses; because health-care professionals are known to be poor proxies for patients, this study was similarly excluded from consideration for the base-case analysis.…”
Section: Model Parametersmentioning
confidence: 99%
“…Most of these studies were deemed inappropriate for the derivation of the current model recurrence health states because the majority either reported only utilities derived from the EORTC QLC-C30 questionnaire (a cancer-specific health-related quality-of-life questionnaire), which cannot be easily converted in to EQ-5D utilities, [78][79][80][81] or did not report health state utilities that could be reliably mapped to the health states used in the current model. 82 One UK study 83 was identified. However, this study calculated EQ-5D utilities from a sample of 50 oncology nurses; because health-care professionals are known to be poor proxies for patients, this study was similarly excluded from consideration for the base-case analysis.…”
Section: Model Parametersmentioning
confidence: 99%
“…Therefore, investigators have started to add these agents in induction chemotherapy regimens. Several phase II and III trials have indicated that taxanes plus cisplatin and fluorouracil (TPF) might be more efficacious and cost-effective than the PF regimen [17], [18], [19], [20], [24], [25]. However, in 2009, Pointreau et al [13] reported another phase III study that demonstrated no significant difference in the 3-year overall survival between regimens (60% in each arm), and the disease-free interval in patients suffering laryngeal or hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Posner et al [151] (TAX324) showed, in 501 patients with locally advanced HNSCC, that induction therapy with a TPF triple combination (docetaxel, cisplatin and 5-FU), compared with the “tried and tested” treatment regimen consisting of a combination of cisplatin and 5-FU (PF), produced a more than two-fold increase in median survival time (70.6 vs. 30.1 months) in a relatively cost-effective manner [143]. This was equivalent to a 30% relative reduction in the risk of death.…”
Section: Cytostaticsmentioning
confidence: 99%